Motivation Effect on UMKM Performance in Banjarmasin City: Overview of Locus of Control as a Contingency Factor - Titien Agustina; Grahita Chandrarin; Abdul Manan (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Globalization affects business and their proprietors, including Micro, Small and MediumEnterprises (MUMKM). This requires businessmen to be responsive, ready to change andadapt to the change itself as business competition is fierce. Should businessman does not makechanges and fix their motivation and character in these conditions, it will have an impact onachieved business performance. Should businessman does not want to change, they would berun over by changes itself. In order for the business/company to survive, a businessman musthave the carrying capacity of character/personality to face the business environment pressure.The self-carrying capacity is the most important aspect. It is the motivation of a UMKM actorto produce a good performance. In addition, this study also reviews the locus of control as acontingency factor that affects business performance. This study aims to analyze the influenceof motivation on UMKM performance in Banjarmasin by reviewing locus of control as acontingency factor. This study used 100 businessmen possessing status as manager and orUMKM business owners in Banjarmasin City as samples. Data collection process utilizedquestionnaires method. Data were collected and processed using moderating regressionanalysis (MRA) and interaction regression between variables. Research results exhibitedmotivation and locus of control possessing a positive effect on business performance. Howeverthe locus of control as a contingency factor which does not prove to be moderating betweenthe motivations of business performance.